Digital Minimalism: Filosofi Efisiensi Penggunaan Teknologi Digital - Muhammad Ilham Nurhakim; Masduki Asbari (Yayasan Aya Sophia Indonesia, 2023)
Digital minimalism is a concept that encourages us to minimize the use of digital technology in our lives so that we can be more focused and productive. This study aims to explain Marissa Anita's perspective from the Greatmind Youtube channel entitled “On Marissa`s Mind: Digital Minimalism”. In this study, researchers used descriptive qualitative methods by recording and listening to material sourced from videos, and material obtained by listening to stories orally. The results of this research explain that digital minimalism is a philosophy of using technology where a person focuses his online time only on a handful of activities that he has chosen carefully and brings optimal benefits to himself. In other words, a digital minimalist is happy to ignore all online activities that do not add value to him.